Saving paradise: Could Detroit be the New Jerusalem?. (August 2017) - Phillips, Tim
The church has inherited a conflicted understanding of "city" both from its biblical roots and from its experience in modern America. John's vision in Revelation could be a window for both resisting a retreat from the city and imagining "city" in new spiritual terms. Much depends on what we think we are looking for. Using reports about the present state of affairs in Detroit as a living commentary on John's vision of a New Jerusalem, what are the "former things" that have "passed away?" What needs to pass away for imagining a new city—a New Jerusalem? What glimpses are there of that new reality? Adapted from a sermon in 2010, this article attempts to name the questions and to kindle some imagination about a new spirituality for the city.